From Epicureanism to Stoicism: Central European Literary Responses to History of the Twentieth Century and Exile (Sándor Márai, Joseph Roth and Stefan Zweig) - Aleksandra Tobiasz (European Journal of Life Writing)
The article addresses Central European historical experiences of the twentieth century manifesting in the fates of Sándor Márai, Joseph Roth and Stefan Zweig. Entangled in the speeding wheel of the modern history, the three writers experienced excessive historical discontinuities (wars, revolutions, dictatorships) which they conceptualized in terms of Epicureanism and Stoicism. To a great extent mythicized Epicurean ‘lightness of being,’ carefree travelling, journalistic openness coexist with the Stoic inward diaristic safeguarding of the self from the historical burden in their texts. While in the Epicurean approach to life, individual is a master of his own fate realizing positive freedom, the centripetal Stoic worldview entails a search of negative freedom from the overwhelming historical fate and a withdrawal to inner (diaristic) self as the only anchor in volatile times. Moreover, the three writers’ historical experiences shaped their double displacement. Whereas its spatial dimension (exilic nomadism) made their self-identifications oscillate between homo politicus and homo poeticus, its temporal aspect – in the article’s foreground – implied the need to narratively inscribe one’s self within a meaningful order of time reconfigured in personal writing.